Effects of received social support on athletes's psychological well-being - Katagami, E.; Tsuchiya, H. (International Journal of Sport & Health Science, 2017)
Although the importance of social support has been broadly recognised within the sports field, its mechanism has not yet been fully examined in terms of identifying effective dimensions, providers and timing. The current study`s aim was to investigate the received support experienced by university student athletes respectively from coaches and teammates over the course of a week, and examine its relationship with self-confidence and feelings of adaptation. Two hundred thirty-one university student athletes completed questionnaires including the Japanese version of the Athlete Received Support Questionnaire (the ARSQ-J). The results indicated that received support might influence recipients` self-confidence both positively and negatively, depending on its dimensions and providers. Esteem support both from coaches and teammates were effective for self-confidence. Tangible support had a positive impact if provided from teammates, but a negative impact if provided by coaches. With regard to the feelings of adaptation, it was indicated that tangible support both from coaches and teammates were negatively correlated with the outcome. In conclusion, its dimension and provider of support can determine the effectiveness of social support. Further clarification of received support in a sport context by examining its dimensions, providers and contexts will contribute to the identification of effective support, which may be useful in supporting athletes.